Aging and Disability Among Hispanics in the United States: Current Knowledge and Future Directions. Issue 2 (30th October 2017) - Garcia, Marc A; Downer, Brian; Crowe, Michael; Markides, Kyriakos S
Abstract: Background and Objectives: Hispanics are the most rapidly aging minority population in the United States. Our objective is to provide a summary of current knowledge regarding disability among Hispanics, and to propose an agenda for future research. Research Design and Methods: A literature review was conducted to identify major areas of research. A life course perspective and the Hispanic Paradox were used as frameworks for the literature review and for identifying future areas of research. Results: Four research areas were identified: (1) Ethnic disparities in disability; (2) Heterogeneity of the U.S. older Hispanic population; (3) Risk factors for disability; and (4) Disabled life expectancy. Older Hispanics are more likely than non-Hispanic whites to be disabled or to become disabled. Disability varied by country of origin, nativity, age of migration, and duration in the United States. Important risk factors for disability included chronic health conditions, depression, and cognitive impairment. Protective factors included positive affect and physical activity. Older Hispanics have longer life expectancy than non-Hispanic whites but spend a greater proportion of old age disabled. Future research should continue to monitor trends in disability as younger generations of Hispanics reach old age. Attention needs to be given to regional variation within the United States for disability prevalence, early-life risk factors, and factors that may contribute to variation in disabled life expectancy. There is also an urgent need for interventions that can effectively prevent or delay the onset of disability in older Hispanics. Discussion and Implications: Considerable research has examined disability among older Hispanics, but continued research is needed. It is important that research findings be used to inform public policies that can address the burden of disability for older Hispanic populations.